(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Hypertensive disorders of pregnancy are responsible for a significant proportion of maternal and prenatal morbidity and mortality. About 7-10 percent of all pregnancies are complicated by hypertensive disorders. Out of these about 5-15% cases are complicated by proteinuria which further increases the maternal and fetal risks. A prospective study was carried out from sept 1996 to feb 2010 at jinnah hosp. Services hosp ch. Rehmat ali teaching hosp lahore and mumtaz bakhtawar hosp. Lahore.total no of patients included in this study was 314.they were divided into two groups.in group a patients with gestational hypertension without proteinuria were included and their no was 194.in group b there were 120 patients diagnosed to have gestational hypertension with proteinuria.the purpose of this study was to estimate and compare the fetal outcome in these two groups